PENINGKATAN KOMPETENSI GURU MENJADI GURU PROFESIONAL - Yazidul Busthomi (JURNAL PUSAKA, 2016)
Generally, the duties and responsibilities of a teacher is to develop intelligence that exists within every student. This intelligence must be developed so thatstudents can grow, can be smart human and ready to face any challenge in the future. Given the duties and responsibilities of teachers are so complex,then a professional teacher is required to have some specific competencies, namely; 1) Pedagogic competence, 2) Personal competence, 3) Professionalcompetence, 4) Social competence. The development and the improvement of teacher’s competence is done through a system of coaching and sustainable development of teacher’s professionalism associated with the acquisition of credit rate functional position. Activities to obtain credit number of functional position obtained by teachers at least via: 1) Collective activities that improve the competence of teachers and/or teacher professionalism. 2) Education and training. 3) Apprenticeship. 4) Scientific publications on the results of researches or innovative ideas. 5) Innovative works. 6) Presentation at the scientific forum. 7) Publication of textbooks that passes the assessment by the national standards bodies of education. 8) The publication of enrichment. 9) Publication of teachers’ manuals. 10) Publication of field experience in special education and/or special education services. 11) Recognition for the accomplishment or dedication as teacher provided by the government. Keywords : Teacher, Competence, Professional